Philosophical Analysis in Latin America
XII, 431 p.
Keywords: Historians of Latin American philosophy have paid relatively little attention to the development of philosophical analysis in Latin America. There are two reasons for this neglect: First, they have been primarily concerned with the forma tive period of philosophical development, in particular with the so called "founders" of La ti n American philosophy. And second. philosophical analysis did not become a noticeable philosophical trend in Latin America until recent years. True. a nunber of Latin American philosophers took notice of Moore. Russell. the members of the Vienna Circle and other important figures in the analytic movement qui te early. But these were isolated instances that lacked the sustained effort and broad base indispensible to make a serious impact in the development of Latin American philosophy. That has changed now. There are not only good numbers of philosophers who work within the analytic tradition, but also some journals and institutes dedicated to the analytic mode of philosophizing. It is. therefore. most appropriate to publish a collection of articles which would introduce the reader of philosophy to the most representative analytic material produced so far in Latin America. Indeed. it is not only appropriate. but also necessary. since most of the published analytic literature to date is scattered in various journals, sometimes of difficult access. Moreover, not all that has been published is representative of the best already produced and of the potential that the movement has in Latin America.